SINTESIS BIOADITIF GASOLINE MELALUI KETALISASI GLISEROL MENGGUNAKAN KATALISATOR PADAT - Nuryoto, Nuryoto; Sulistyo, Hary; Sediawan, Wahyudi Budi; Perdana, Indra (Universitas Negeri Semarang, 2016)
Utilization of glycerol side product from biodiesel as waste management application is required for reduced negative effect which possible emerged. Glycerol have three bond of hydroxyde, so its opportunity to utilize to be solketal as bio-additive of gasoline. Indion 225 Na ion exchanger resin is strong acid cation category and low prices, so its potency to use alternatively of solid catalyst to get efficient and economic process. The purpose of this research was focussed to search of the best condition by optimalization indion 225 Na performance as catalyst in glycerol ketalization reaction, by integrated of variables that have effected to reaction for maximize glycerol coversion. To get maximize of reactants molecular interaction and for optimalization indion 255 Na performance, observation conducted in the range variables which widely enough that were reactant ratio of 5:1-6:1 mole of acetone mole/mole of glycerol, diameter size catalyst of 20-40 mesh, catalyst concentration of 3-5% mass of acetone, and reaction temperature of 35-65oC. Result of the research showed that indion 225 Na catalyst have good performance, by glycerol conversion to reach of 51.89%. Glycerol conversion mentioned was obtained at reactant ratio of 6:1 mole of acetone/mole of gycerol, diameter size catalyst of 40 mesh, catalyst concentration of 4% mass of acetone, and reaction temperature of 65oC.